DEKRIT PRESIDEN (Studi Perbandingan Dekrit 5 Juli 1959 dengan Dekrit Presiden 23 Juli 2001) - Musta’in Ramli; Sumiyatun Sumiyatun (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Presidential Decree 5 July 1959 (Sukarno) was a decree issued by the President of Indonesia, Sukarno on 5 July 1959. The contents of the decree is the dissolution of the Constituent body of the 1955 election results and the replacement of the Uasar Act of 1950 to the Temporary CONSTITUTION of UUD ' 45. While the Presidential Decree of 23 July 2001 (k. h. Abdurrahman Wahid) is the presidential decree issued by President k. h. Abdurrahman Wahid, as resistance anterior to the decision I and II of the Memorandum issued by the HOUSE of REPRESENTATIVES. But eventually the Decree k. h. Abdurrahman Wahid could not be accepted by the House and ended with the fall of the presidential chair k. h. Abdurrahman Wahid.